1993
DOI: 10.1016/0925-4773(93)90023-q
|View full text |Cite
|
Sign up to set email alerts
|

A universal target sequence is bound in vitro by diverse homeodomains

Abstract: To determine the number of DNA binding proteins capable of binding a consensus Engrailed binding site, this consensus sequence was used to screen a library of Drosophila cDNA clones in a bacteriophage expression vector. We retrieved clones encoding 20 distinct DNA binding domains, 17 of which are homeodomains. Binding to a variety of oligonucleotides confirms the related sequence specificity of the retrieved binding domains. Nonetheless, the homeodomains have remarkably diverse amino acid sequences. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 66 publications
1
53
0
Order By: Relevance
“…After the identification of the genes encoding several adhesion molecules, such as cytotactin (30), N-CAM (31,32), and L-CAM (25), as target genes for homeoproteins (33), our results indicate that bFGF is the first growth factor involved in the complex network underlying HOX gene effects on cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the identification of the genes encoding several adhesion molecules, such as cytotactin (30), N-CAM (31,32), and L-CAM (25), as target genes for homeoproteins (33), our results indicate that bFGF is the first growth factor involved in the complex network underlying HOX gene effects on cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…5 indicated a direct and selective interaction of the HOXB7 protein with the sequence encompassing nucleotides ϩ130 to ϩ159 of the bFGF promoter. Although the ATTA box is shared among several homeoproteins (33), unique flanking sequences may account for their high-affinity binding.…”
Section: Resultsmentioning
confidence: 99%
“…The initial dri cDNA clone (bk60) was isolated as described previously (16). Subsequent overlapping clones were isolated by screening a gt11 Drosophila 3-to 18-h embryo cDNA library (Clontech) with regions of bk60 as the probes.…”
Section: Methodsmentioning
confidence: 99%
“…The similarity of the in vitro DNA-binding characteristics of homeodomain proteins was particularly evident in a screen that identified a large number of homeodomain proteins by their ability to bind an oligonucleotide containing a consensus EN binding site (16). One of the genes identified in that screen, originally termed bk60 but here renamed dead ringer (dri), is the subject of this report.…”
mentioning
confidence: 99%
“…Experiments indicated that Sox and POU proteins work together to activate, while homeodomain proteins repress and limit expression of CNS genes. Interestingly, several motifs identified here as important for regulation in midline glia of Drosophila resemble binding sites for Sox (G1: CACAAT; Wegner 1999), POU (G4: ATGCAAAT, G6: ATGCAACA, and G8: ATGCGTGG; Pankratova and Polanovsky 1998), and homeodomain proteins (G5: ATTTTATC; Kalionis and O'Farrell 1993).…”
Section: Discussionmentioning
confidence: 99%